2014
DOI: 10.1186/1475-2840-13-67
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of subcutaneous abdominal fat on ultrasonography to carotid atherosclerosis in patients with type 2 diabetes mellitus

Abstract: BackgroundWhereas visceral abdominal adipose tissue (VAT) is associated with cardiometabolic risk, there is debate regarding the role of subcutaneous abdominal adipose tissue (SAT). The aim of this study was to investigate the relationships of subcutaneous and visceral abdominal fat with carotid atherosclerosis in patients with type 2 diabetes mellitus (T2DM).MethodsA total of 234 patients (men 131, women 103, mean age: 53 years) with T2DM were enrolled. Carotid intima-media thickness (CIMT), abdominal subcuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
2
20
0
2
Order By: Relevance
“…Furthermore, none of the patients evaluated in our study were obese, and BMI was not associated with CIMT or carotid plaques. These results suggest that the pattern of central fat deposition in type 1 DM may also be associated with increased risk of atherosclerotic CVD and negative metabolic effects, similar to the findings described in type 2 DM patients (8,(22)(23)(24).…”
Section: Resultssupporting
confidence: 76%
“…Furthermore, none of the patients evaluated in our study were obese, and BMI was not associated with CIMT or carotid plaques. These results suggest that the pattern of central fat deposition in type 1 DM may also be associated with increased risk of atherosclerotic CVD and negative metabolic effects, similar to the findings described in type 2 DM patients (8,(22)(23)(24).…”
Section: Resultssupporting
confidence: 76%
“…Moreover, the possible protective role of subcutaneous fat against subclinical atherosclerosis, which was not measured in our study, might have affected our results. [27]. Finally, current obesity, rather than its duration, may be the most important precursor of clinical cardiovascular and metabolic outcomes [28].…”
Section: Discussionmentioning
confidence: 99%
“…It was considered that this type of obesity increased the risk of pathological changes in other systems along with the progress of T2DM. [10][11][12] Attention should be paid to the distribution of subcutaneous adipose tissue in patients with T2DM. We found that in patients with T2DM the accumulation of subcutaneous adipose tissue was primarily in torso and less so in the limbs.…”
Section: Discussionmentioning
confidence: 99%